New Chaetoglobosins with Fungicidal Activity from Chaetomium sp. UJN-EF006 Endophytic in Vaccinium bracteatum - Luo-Jing Wang; Zong-Yan Ma; Xin-Ling Wang; Kai-Le Wang; Tong Zhang; Rui-Ying Han; Jun-Jiang Li; Jie Bao; Yin-Yin Wang; Hua Zhang (Journal of Fungi, 2025)
Nine chaetoglobosins (1–9) including five previously undescribed ones (1–5) were obtained from the culture broth of an endophytic fungus (Chaetomium sp. UJN-EF006) isolated from the leaves of Vaccinium bracteatum. The structures of these fungal metabolites were elucidated by spectroscopic methods including mass spectroscopy, nuclear magnetic resonance, single crystal X-ray crystallography, and electronic circular dichroism. To accelerate the development of novel fungicides, all of the isolated chaetoglobosins were evaluated for their antifungal activity against two crop pathogens, Botrytis cinerea and Sclerotinia sclerotiorum. The assay results revealed that chaetoglobosins 2, 6, 7, and 9 possessed a significant fungicidal effect against B. cinerea, with EC50 values all below 10 μg/mL. Particularly, the most potent compound, 7, was 175- and 96-fold as active as the commercially available fungicides carbendazim (EC50 70.11 μg/mL) and azoxystrobin (EC50 39.02 μg/mL), respectively. A further observation under scanning electron microscope indicated that compound 2 could markedly impair the fungal hyphae of B. cinerea. The study demonstrates that the chaetoglobosins had excellent in vitro antifungal activities against B. cinerea.